THE ROLE OF HUMIC SUBSTANCES IN THE TRANSPORT AND FIXATION OF METALS OF ECONOMIC INTEREST (AU, PT, PD, U, V) - Wood S.A. (My University, 1996)
Humic substances are complicated, naturally occurring organic compounds of high molecular weight. Owing to the presence of functional groups containing oxygen, and to a lesser extent, nitrogen and sulfur, these substances are capable of interacting with economically interesting metals in solution in a number of ways. Humic substances may: (1) form soluble complexes with metal ions; (2) cause precipitation of metal ions via reduction; (3) cause precipitation of metal ions via adsorption, ion exchange or other sorption processes (when humic substances themselves are insoluble); (4) modify the sorption behavior of mineral surfaces with respect to metal ions; (5) modify the behavior of colloidal particles of metals; and (6) affect the rates of geological processes. The ability to develop quantitative geochemical models of these interactions is important in the study of the secondary dispersion of most ore metals in the surficial environment and of primary ore-forming processes for a number of ore metals (e.g., Au, PGE, U, V). Available data suggest that humic substances are drastically altered, especially with respect to their ability to complex metals, at temperatures exceeding about 100°C, so their role is probably limited to low temperature environments. In this review, attention is focussed on the binding and reducing effects of humic substances on Au, PGE, U and V.